Peningkatan Keterampilan Berbicara Melalui Model Pembelajaran Picture And Picture Pada Siswa Kelas IV MIN 1 Banda Aceh - Fitri Ramadani; Amandha Fhadilla Siregar; Zelma Azahra (Universitas Maritim AMNI Semarang, 2023)
Talking is one of the activities that most humans do in relation to social life. The picture and picture learning model in presenting learning media in the form of pictures. This study aims to improve speaking skills with the picture and picture learning model in grade IV MIN 1 Banda Aceh students. This research is a Class Action Research which consists of two cycles where each cycle is held in two meetings. Research procedures include planning, implementation of action, observation and reflection. The subjects in this study were 24 students of class IV MIN 1 Banda Aceh g. The results showed that in the first cycle that was completed individually, of the 24 students, only 5 students, 20.83%, met the minimum completeness criteria (KKM) or were in the very low category. Classically it has not been fulfilled because the average value obtained is 58.59%. Whereas in the second cycle where out of 24 students as a whole have met the minimum completeness criteria with an average obtained of 76.75% or are in the high category. Based on the results of this study, it can be concluded that the speaking skills of grade IV students at Min 1 Banda Aceh through the application of the picture and picture learning model have increased.